Changes in well-being around elections - Nicolas Schreiner (University of Basel, Center of Business and Economics (WWZ), 2021)
Elections constitute the essential element of democracy, yet surprisingly little is known about their immediate consequences for individual well-being. Cross-country empirical evidence is particularly absent for the campaign period leading up to elections. While elections as a process allow citizens to contribute to democratic quality, they are also intrinsically conflictual and require voters to exert effort to make informed decisions. To measure the aggregate changes in well-being along the entirety of the electoral process, I use survey data from before and after 148 national elections in 24 European countries between 1989 and 2019. Respondents interviewed in the months preceding election day report significantly lower levels of life satisfaction than their compatriots asked the same calendar week but in years without elections. Once voting has taken place, aggregate well-being immediately returns to its regular average. Exploratory analyses suggest that partisan conflict and social pressures regarding democratic participation may play a role in explaining the reduction in life satisfaction before elections.
Keywords: D72; D91; I31; 330; elections; well-being; life satisfaction; election campaigns; electoral systems; political polarization; eurobarometer